THE OXYGEN ISOTOPIC COMPOSITION OF OLIVINE AND PYROXENE FROM CI CHONDRITES - Leshin L.A.; Rubin A.E.; McKeegan K.D. (My University, 1997)
The CI chondrites are taken to represent average solar system material based on the similarity of their elemental compositions to that of the solar photosphere. However, their oxygen isotope geochemistry is dominated by secondary minerals that formed during aqueous alteration on the CI parent body. Precursors to this alteration, namely olivine and pyroxene, are extremely rare in CI chondrites, precluding previous measurements of their oxygen isotopic composition. We report ion microprobe analyses of oxygen isotopes in single olivine and pyroxene grains separated from CI chondrites Orgueil and Ivuna.The CI chondrite olivine and pyroxene grains most likely represent liberated chondrule phenocrysts, based on petrographic, chemical, and isotopic evidence consistent with crystallization from a melt. The oxygen isotope data form an array that falls nearly along the carbonaceous chondrite 16O mixing line with δ18O values ranging from -9.3%% to +12.3%% and δ17O from -11.3%% to +7.8%%, consistent with nebular processes being the source of the oxygen isotopic compositions. The degree of 16O-enrichment in Orgueil olivines is negatively correlated with FeO content, but the exact nature and timing of the process that introduced this variation remains unknown. The pyroxene oxygen isotopic compositions are similar to those of olivines with >5 mol% fayalite.The oxygen isotopic analyses of the olivine and pyroxene in CI chondrites have been used to revise previous models for the isotopic evolution of CI materials. Our data require more complete gas-solid equilibration in the nebula and constrain the initial aqueous fluids on the CI parent body to have lower Δ17O values than previously postulated. The refined model indicates that the temperature of aqueous activity on the CI parent body was no higher than ~50°C, and the fluid:rock ratio was significantly less than previously estimated. Even prior to alteration and formation of secondary minerals, the CI chondrites were the most 16O-depleted carbonaceous chondrites and thus the solids originally contained in the CI chondrites are the most equilibrated nebular materials represented in the carbonaceous chondrites. The data suggest the oxygen isotopic composition of average solar system to be approximately equivalent to average terrestrial oxygen as recorded in the compositions of terrestrial and lunar basalts.